Optimalisasi Pemberdayaan Bagi Orang Tua Melalui Pelatihan Membaca Al-Qur’an Dengan Metode Tilawati - Zaeni, Akhmad; Maulana, Fatih Amri; Hotijah, Siti (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2022)
Empowerment in general can be interpreted as power, strength and ability. While the parents are the father or mother. both biological, adopted, step-in-law and in-laws. But in this study, parents are defined as people whose age has entered old age, whether they include the mother or father or not. Empowerment of parents in reading the Qur'an needs to be developed and optimized. Because the optimization of reading the Qur'an does not look at age, both children, adolescents and parents need to continue to be optimized and developed. Here we do community service with the theme "Optimizing Empowerment for Parents Through Reading the Qur'an With the Tilawati Method in Wonorejo Village". So here we provide direction or guidance related to these problems. In implementing the Empowerment for Parents service program through reading the Qur'an, we use the EBR (Empowerment-Based Research) research method where in this EBR method there are 4 stages, including exploration, create and action, evaluation and report and dissemination. . The results of the parent empowerment program in Wonorejo Village are in accordance with the goals that have been set by us, namely so that parents can still learn to read the Qur'an correctly and fluently according to the rules of tajwid optimally even though they are quite old. So it is necessary to have a method of empowerment. So we chose the Tilawati method in the study, so that the empowerment of learning to read the Qur'an for elderly people in Wonorejo Village is optimal. And then it can be continued by the teachers and cadres that have been formed.